Practice and Malpractice: Physician Responses to the Liability 'Crisis' - Lynne Cossman; Debra Street (Journal of Public and Professional Sociology)
Mississippi is a largely rural state with many poor and unhealthy residents who are chronically underserved by the smallest per capita physician workforce in the nation. Anecdotal reports claimed Mississippi‘s medical malpractice climate jeopardized patient access to health care even further. Using survey data from Mississippi physicians, we document how medical liability perceptions shaped their practices at the height of the Mississippi malpractice crisis. Our findings show that physicians‘ risk profiles strongly influenced the extent to which physicians reported practicing defensive medicine or considered relocating or retiring early in response to malpractice conditions. This raises the specter of further compromising access to physician care in an already underserved state.